2019
DOI: 10.1103/physrevb.99.014510
|View full text |Cite
|
Sign up to set email alerts
|

Dominant s -wave superconducting gap in PdTe2 observed by tunneling spectroscopy on side junctions

Abstract: We have fabricated superconductor-normal metal side-junctions with different barrier transparencies out of PdTe2 crystalline flakes and measured the differential conductance spectra. Modeling our measurements using a modified Blonder Tinkham Klapwijk (BTK) formalism confirms that the superconductivity is mostly comprised of the conventional s-wave symmetry. We have found that for junctions with very low barrier transparencies, the junctions can enter a thermal regime, where the critical current becomes importa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…Lower panel: Ac-susceptibility at p = 2.07 GPa measured in applied magnetic fields. Curves from right to left in 0 mT to 7 mT with 1 mT steps and in10,13,16,19,22, 25 and 28 mT.…”
mentioning
confidence: 99%
“…Lower panel: Ac-susceptibility at p = 2.07 GPa measured in applied magnetic fields. Curves from right to left in 0 mT to 7 mT with 1 mT steps and in10,13,16,19,22, 25 and 28 mT.…”
mentioning
confidence: 99%
“…Peculiarly, from resistance measurements a critical field B R c (0) = 0.32 T was deduced. Weak-coupling conventional superconductivity in PdTe 2 was demonstrated via measurements of the heat capacity [12,15], penetration depth [16,17], scanning tunneling microscopy and spectroscopy (STM/STS) [9,18,19], and side junction tunneling spectroscopy [20]. Superconductivity is partly attributed to a van Hove singularity situated at ∼ 30 meV above the Fermi level [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The superconducting properties of PdTe 2 have been widely investigated at ambient pressure [7,8,[10][11][12][13][14][15][16][17][18][19]. PdTe 2 is a type-I superconductor with T c = 1.64 K and its critical field µ 0 H c (T ) follows the standard quadratic temperature variation with µ 0 H c (0) = 13.6 mT [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is considered that a saddle-point van Hove singularity (vHs) near the * E-mail: ohmura@phys.sc.niigata-u.ac.jp M -point in the Brillouin zone, which is located about 30 meV above the Fermi level [20], plays an important role in the conventional Bardeen-Cooper-Schrieffer (BCS) behavior [14]. Meanwhile, as regards the surface states of PdTe 2 , its superconducting properties are under discussion [7,8,10,[15][16][17]. Leng et al observed an unusual surface sheath superconductivity in ac-susceptibility measurements in magnetic fields [10].…”
Section: Introductionmentioning
confidence: 99%